Economic evaluation of prebiotics, probiotics and symbiotics in juvenile Nile tilapia - Azevedo, Rafael; Fosse Filho, João; Cardoso, Leonardo; Mattos, Douglas; Vidal Júnior, Manuel; Andrade, Dalcio (Revista Ciência Agronômica, 2014)
This study aimed to evaluate economically the inclusion of prebiotics, probiotics and symbiotics in diets of Nile tilapia (4.07 ± 0.30 g), at two stocking densities (0.6 and 1.2 kg m-3). A total of 288 fish were distributed over 32 tanks (40 L) in a completely randomised design, in a 2 x 4 factorial (stocking density x additives), with four replications, over six weeks. The following were evaluated: total feed consumption (FC), final biomass (FB), relative gain in biomass (RGB), apparent feed conversion (AFC), survival rate (SUR), average cost of feed per kg of live weight gain (ACF), total cost of feed (TCF), total cost of production (TCP), gross income (GI), operating profit (OP) and economic efficiency index (EEI). No effect was seen on the evaluated parameters from the interaction (p>0.05) between stocking density and inclusion of the feed additives. No influence was observed (p>0.05) on SUR from the stocking density, although this significantly influenced the parameters FB, FC, RGB, AFC, ACF, TCF, TCP, GI and OP. There was no significant influence from the inclusion of prebiotics, probiotics and symbiotics on FC, SUR and TCF, however there was an influence (p